Patterns of Antibiotic Resistance in Enterobacteriaceae Isolates from Broiler Chicken in the West Region of Cameroon: A Cross-Sectional Study - Jude Fonbah Leinyuy; Innocent Mbulli Ali; Ousenu Karimo; Christopher B. Tume (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The emergence of multidrug-resistant food-borne pathogens of animal origin including Enterobacteriaceae is a growing concern. Identifying and monitoring resistance in isolates from human-related environments are of clinical and epidemiological significance in containing antimicrobial resistance. This study aimed to contribute towards the fight against antibiotic resistance and ameliorate the management/treatment of Enterobacteriaceae-linked diseases in Cameroon. Methods. Cloacal swabs from healthy broilers were enriched in buffered-peptone-water and cultured on EMB agar. Antibiotic susceptibility was tested on Mueller-Hinton-Agar by disc diffusion. Plasmid-borne genes for extended-spectrum beta lactamase (ESBL) and resistance to Quinolones (PMQR) and Aminoglycosides were detected by standard endpoint polymerase chain reaction (PCR). Results. A total of 394 isolates were identified belonging to 12 Enterobacteriaceae genera, the most prevalent were Escherichia coli (81/394 = 20.56%), Salmonella spp (74/394 = 18.78%), and Klebsiella spp (39/394 = 9.90%) respectively. Overall, 84/394 (21.32%) were ESBL producers, 164/394 (41.62%) were resistant to quinolones, 66/394 (16.75%) resistant to aminoglycosides with 44.0% (173/394) expressing MDR phenotype. Poor hygiene practice (OR 2.55, 95% CI: 1.67, 3.89, p=0.001) and rearing for >45 days, (OR = 7.98, 95% CI: 5.05, 12.6, p=0.001) were associated with increased carriage of MDR. Plasmid-borne resistance genes were detected in 76/84 (90.48%) of ESBL-producing isolates, 151/164 (92.07%) quinolone resistant isolates and 59/66 (89.39%) aminoglycoside resistant isolates with co-occurrence of two or more genes per isolate in 58/84 (69.05%) of ESBLs, 132/164 (80.49%) of quinolone resistant isolates and 28/66 (42.42%) of aminoglycoside resistant isolates. Conclusion. This study found high carriage and widespread distribution of Enterobacteriaceae with ESBL and MDR in broiler chicken in the West Region of Cameroon. Most PMQR genes in bacteria were found at levels higher than is seen elsewhere, representing a risk in the wider human community.